Successful phage-antibiotic therapy of P. aeruginosa implant-associated infection in a Siamese cat - Ron Braunstein; Goran Hubanic; Ortal Yerushalmy; Sivan Oren-Alkalay; Amit Rimon; Shunit Coppenhagen-Glazer; Ofir Niv; Hilik Marom; Alin Barsheshet; Ronen Hazan (Veterinary Quarterly)
Antibiotic-resistant pathogens are a growing global issue, leading to untreatable infectious diseases in both humans and animals. Personalized bacteriophage (phage) therapy, the use of specific anti-bacterial viruses, is currently a leading approach to combat antibiotic-resistant infections. The implementation of phage therapy has primarily been focused on humans, almost neglecting the impact of such infections on the health and welfare of companion animals. Pets also have the potential to spread resistant infections to their owners or the veterinary staff through zoonotic transmission. Here, we showcase personalized phage-antibiotic treatment of a cat with a multidrug-resistant Pseudomonas aeruginosa implant-associated infection post-arthrodesis surgery. The treatment encompassed a tailored combination of an anti-P. aeruginosa phage and ceftazidime, precisely matched to the pathogen. The phage was topically applied to the surgical wound while the antibiotic was administered intramuscularly. After two treatment courses spanning 7 and 3 weeks, the surgical wound, which had previously remained open for five months, fully closed. To the best of our knowledge, this is the first case of personalized phage therapy application in felines, which provides further evidence of the effectiveness of this approach. The successful outcome paves the way for personalized phage-antibiotic treatments against persistent infections therapy in veterinary practice.